2022
DOI: 10.1155/2022/9399658
|View full text |Cite|
|
Sign up to set email alerts
|

Chrysophanol Ameliorates Hemin-Induced Oxidative Stress and Endoplasmic Reticulum Stress by Regulating MicroRNA-320-5p/Wnt3a Pathway in HT22 Cells

Abstract: Oxidative stress, endoplasmic reticulum (ER) stress, and neuronal cell apoptosis have been considered as the main pathogenesis factors of brain injury after intracerebral hemorrhage (ICH). Chrysophanol (CHR) has been proved to have neuroprotective effects, but the role and underlying mechanisms of CHR in ICH remain unclear. HT22 cells were dealt with hemin to mimic an in vitro ICH model and then subjected to treatment with or without CHR. The cell viability, apoptosis, ER stress, and oxidative stress were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 78 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…In order to unravel the internal mechanism of Egr1 and Phlda1 in ICH, we first built an ICH cell model and preliminarily investigated the expression status of Egr1 and Phlda1 within ICH. We exposed HT22 cells to hemin to establish an ICH cell model, based on previous studies [20][21][22]. It was found that both the mRNA and protein levels of Egr1 and Phlda1 were upregulated in hemin-treated HT22 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to unravel the internal mechanism of Egr1 and Phlda1 in ICH, we first built an ICH cell model and preliminarily investigated the expression status of Egr1 and Phlda1 within ICH. We exposed HT22 cells to hemin to establish an ICH cell model, based on previous studies [20][21][22]. It was found that both the mRNA and protein levels of Egr1 and Phlda1 were upregulated in hemin-treated HT22 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cells were grown in DMEM/ F12 medium (CORNING, with 10% FBS and 1% penicillin/streptomycin) and maintained in a 5% CO 2 environment at 37 °C. To simulate ICH in vitro, cells were treated with 20 μM hemin (Sigma, California, USA) for 6 h, as previously described [20].…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…Firstly, it is notable that in vivo tests were not performed. Interestingly, many previous studies have also used cell experiments alone to investigate brain injury [33,43,55]. Therefore, the experiments in vitro can reveal the related mechanism of the neuroprotection of hydrogen at a certain level.…”
Section: Discussionmentioning
confidence: 99%
“…HT22 cell, an immortalized mouse hippocampal neuronal cell line, was subcloned from parent HT4 cells originally immortalized from cultures of primary mouse hippocampal neurons [33]. HT22 cell was obtained from the Laboratory of Anesthesiology, Southwest Medical University (Luzhou, China).…”
Section: Cell Culturementioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%